Yazidi women after August 3, 2014: A study of the role of Yazidi survivors in raising awareness of ISIS crimes against the Yazidis - Maho, Arshad Hamad Maho; Vian, Iyad Ajaj Vian (Sulaimani Journal for Humanities, 2026)
This research addresses the role of Yazidi girls and women survivors who were liberated from ISIS and were then able to reveal the violence that ISIS practiced against them, and the extent of their suffering, such as sexual and psychological torture. After that, internal factors related to the Yazidi community and external factors connected with international organizations, all of these played an essential role in these survivors becoming major activists in the world and also they were able to raise the issue of their people to international bodies. Their attempts and efforts received global attention to inform the international community of the genocide that occurred against the Yazidis. For this reason, these survivors gained great status among the people, and received many honorary medals from the United Nations, European parliaments and other international bodies, as a material and moral reward for them